KOMPETENSI MAHASISWA FT-UNJ UNTUK MELAKSANAKAN PEMBELAJARAN DI SEKOLAH MENENGAH KEJURUAN - Suyitno Muslim (Fakultas Teknik Universitas Negeri Jakarta, 2017)
The objective of the research is to find the correlation between students’ self concept, interest to be teachers, achievement of FT-UNJ students toward the instructional competence in vocational schools. The research was conducted in the Technical Faculty of the State University of Jakarta and the Vocational Schools by the survey method with sixty respondents which selected by simple random sampling. The data are analyzed by regression and correlation procedures. The results of the research conclude: there was positive and significant correlation between students’ self concept, interest to be teachers, and achievement of FT-UNJ students with instructional competence in vocational schools in a partial and together correlation. Achievement instructional competence in vocational schools can be increased by improving the quality of students’ self concept, interest to be teachers, and achievement of FT-UNJ students. Abstrak Tujuan penelitian ini untuk mengetahui keeratan hubungan antara konsep diri, minat menjadi guru, dan prestasi belajar mahasiswa FT-UNJ untuk melaksanakan pembelajaran di sekolah menengah kejuruan. Penelitian ini dilakukan di Fakultas Teknik, Universitas Negeri Jakarta dan di Sekolah Menengah Kejuruan se DKI Jakarta dengan metode survei pada sampel sebanyak 60 orang yang dipilih secara acak sederhana. Data hasil penelitian dianalisis dengan korelasi produk momen dan regresi. Hasil penelitian ini menyimpulkan bahwa ada hubungan positif dan signifikan antara konsep diri, minat menjadi guru, dan prestasi belajar dengan kompetensi mahasiswa FT-UNJ untuk melaksanakan pembelajaran di sekolah menengah kejuruan, baik secara sendiri-sendri maupun bersama-sama. Kompetensi mahasiswa FT-UNJ untuk melaksanakan pembelajaran di sekolah menengah kejuruan dapat ditingkatkan dengan meningkatkan konsep diri, minat menjadi guru, dan prestasi belajar.